2008
DOI: 10.1016/j.compchemeng.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling systems defined by RTD curves

Abstract: The RIO theory is commonly used for describing flow patterns in a large class of applications, and par ticularly for ventilated enclosures. Experimental RIO curves are used for modelling these premises with an application in the nuclear industry for predicting the airbome pollutant transfers in order to prevent radiological risk. An approach based on a superstructure involving interlinked elementary flow patterns such as CS TRs, P FRs, recycles and by-passes is implemented. ln order to propose a generic and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A known tracer distribution is injected in input and measurements of the output give the Residence Time Distribution (RTD) functions as explained in Danckwerts [21]. The analysis of RTD functions gives a possible network of "virtual" ideal reactors that is representative of the global fluid dynamics system (see Figure 1 left) (Hocine et al [37], Laquerbe et al [53]). The representative structure is not necessarily unique and could be improved by getting information such as geometry (reactor shape, size) or mixing device position and energy provided to the fluid.…”
Section: Systemic Approachmentioning
confidence: 99%
“…A known tracer distribution is injected in input and measurements of the output give the Residence Time Distribution (RTD) functions as explained in Danckwerts [21]. The analysis of RTD functions gives a possible network of "virtual" ideal reactors that is representative of the global fluid dynamics system (see Figure 1 left) (Hocine et al [37], Laquerbe et al [53]). The representative structure is not necessarily unique and could be improved by getting information such as geometry (reactor shape, size) or mixing device position and energy provided to the fluid.…”
Section: Systemic Approachmentioning
confidence: 99%
“…Other studies have been recently done to fill in the gaps of classical RTD methods, as Smart RTD (Simcik et al 2012) and the reactive-mixing index analysis (Yablonsky et al, 2009). Yet, Claudel et al (2002) and Hocine et al (2008) developed simple hydrodynamic models through the RTD by making some assumptions about the internal information of the systems in study.…”
Section: 2mentioning
confidence: 99%
“…Two alternative approaches for the direct generation of reactor models worth mentioning have used genetic algorithms (Laquerbe et al 2001) or found a model by simplifying initially complex super-structures (Hocine et al 2008). Both approaches, however, require the measurement of the residence time distribution.…”
Section: Introductionmentioning
confidence: 99%